ENHANCING LANGUAGE LEARNING THROUGH GROUP DISCUSSIONS: A COMMUNAL APPROACH TO FOREIGN LANGUAGE ACQUISITION - Свісюк, Олена; Вергун, Тетяна; Білошітска, Зоя (SWorldJournal, 2024)
In an increasingly interconnected and globalized world, the importance of learning a foreign language is crucial. This paper emphasizes the significance of mastering foreign languages, particularly in the context of students' professional training. Langua